Genera of phytopathogenic fungi: GOPHY 3 - Yasmina Marín-Felix; Margarita Hernández‐Restrepo; Isabel Iturrieta‐González; Dania García; Josepa Gené; J.Z. Groenewald; Lei Cai; Q. Chen; William Quaedvlieg; R.K. Schumacher; P. W. J. Taylor; C Ambers; et al. (2019)
This paper represents the third contribution in the Genera of Phytopathogenic Fungi (GOPHY) series. The series provides morphological descriptions, information about the pathology, distribution, hosts and disease symptoms for the treated genera, as well as primary and secondary DNA barcodes for the currently accepted species included in these. This third paper in the GOPHY series treats 21 genera of phytopathogenic fungi and their relatives including: Allophoma , Alternaria , Brunneosphaerella , Elsinoe , Exserohilum , Neosetophoma , Neostagonospora , Nothophoma , Parastagonospora , Phaeosphaeriopsis , Pleiocarpon , Pyrenophora , Ramichloridium , Seifertia , Seiridium , Septoriella , Setophoma , Stagonosporopsis , Stemphylium , Tubakia and Zasmidium . This study includes three new genera, 42 new species, 23 new combinations, four new names, and three typifications of older names.